A QUALITATIVE SYNTHESIS OF ARTIFICIAL INTELLIGENCE ADOPTION IN MSMES: INSIGHTS INTO OPPORTUNITIES AND CHALLENGES - Purwati, Astri Ayu; Abdullah, Siti Intan Nurdiana Wong; Deli, Mazzlida Mat (Lembaga Riset dan Inovasi Almatani, 2025)
Artificial intelligence (AI) has emerged as a transformative technology that is reshaping business processes, innovation, and competitiveness, particularly for Micro, Small, and Medium Enterprises (MSMEs). Despite its potential, AI adoption among MSMEs remains uneven and is often constrained by various technological, organizational, and environmental factors. This study aims to provide a comprehensive understanding of AI adoption in MSMEs by conducting a qualitative synthesis of existing literature, focusing on the identification of key drivers, barriers, opportunities, and organizational impacts. This research adopts a systematic literature review (SLR) approach, guided by the PRISMA framework, to analyze 25 peer-reviewed articles indexed in Scopus. A thematic analysis was employed to systematically code and categorize the findings, enabling the identification of recurring patterns and critical themes related to AI adoption in MSMEs. The results reveal four major themes: (1) drivers of adoption, including technological readiness, organizational capabilities, competitive pressure, and perceived benefits; (2) barriers to adoption, such as financial constraints, lack of expertise, technological complexity, and organizational resistance; (3) opportunities enabled by AI, including enhanced operational efficiency, improved customer insights, innovation, and market expansion; and (4) organizational impacts, particularly in terms of performance improvement, digital transformation, innovation capability, and strategic alignment. The study contributes to the literature by providing an integrative and qualitative perspective on AI adoption in MSMEs, extending the Technology-Organization-Environment (TOE) framework with AI-specific insights. Practically, the findings offer guidance for MSME managers and policymakers in designing strategies to overcome adoption barriers and leverage AI for sustainable growth. Future research is encouraged to explore empirical and longitudinal approaches to further examine the dynamic nature of AI adoption in MSMEs.